Webinar series a journey with NIRO ceramic group - Bidin, Zafikha Aida (UiTM Sarawak, 2021)
A webinar on “Ajourney with Niro Ceramic Group” was conducted on the 21st May 2020. The webinar was organised by Niro Ceramic Group .It was an open and a free webinar for RISM QS Division Partnering Universities. The second semester students from Bachelor of Quantity Surveying, UiTM Sarawak were invited to join the webinar.